1988
DOI: 10.3354/meps042001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tides on microgrowth bands in Cerastoderma edule from Norway

Abstract: At an intertidal site on the island of Tautra in Trondheimsfjord, Norway, cockles Cerastoderma edule L. were sampled from 121 cm (Stn A) and 66 cm (Stn B) below tidal datum. Shells were sectioned longitudinally, polished, etched and photographed under a scanning microscope to reveal microgrowth bands. Tidal heights were calibrated against a tide recorder in Trondheim harbour, thus providing immersion times and tidal heights for Stns A and B. The tidal and growth band data were subjected to time-series analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Variations in growth rate of molluscs are controlled by environmental factors and physiological constraints (Wilbur and Owen 1964;House and Farrow 1968;Schöne et al 2003). During the year, the growth rates of C. edule fluctuated, mainly due to the variations of sea temperature and the tidal patterns (Cole 1956;House and Farrow 1968;Lönne and Gray 1988). Our study in April however may not have been representative of the whole year.…”
Section: Tidal Rhythm Of Internal Increments Formationmentioning
confidence: 91%
See 3 more Smart Citations
“…Variations in growth rate of molluscs are controlled by environmental factors and physiological constraints (Wilbur and Owen 1964;House and Farrow 1968;Schöne et al 2003). During the year, the growth rates of C. edule fluctuated, mainly due to the variations of sea temperature and the tidal patterns (Cole 1956;House and Farrow 1968;Lönne and Gray 1988). Our study in April however may not have been representative of the whole year.…”
Section: Tidal Rhythm Of Internal Increments Formationmentioning
confidence: 91%
“…Previous studies on C. edule growth addressed the increment formation periodicity (Bourget and Brock 1990), debating whether it follows a tidal (Richardson 1979(Richardson , 1980(Richardson , 1981Lönne and Gray 1988) or a circadian rhythm (Cole 1956;House and Farrow 1968). Different methods have been used (cold shock, time-series analysis, external ring census, etc.…”
Section: Tidal Rhythm Of Internal Increments Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of a sub-daily growth pattern has also been reported in the bivalves C. edule (House and Farrow 1968;Whyte 1975) and Chione cortezi (Goodwin et al 2001;Schöne et al 2002), although its relation with the physiology and periodicity of growth has not yet been established. In some cases, a subdaily growth rhythm has been associated with the presence of tides (Evans 1972(Evans , 1975Richardson et al 1979;Lonne and Gray 1988;Mahe et al 2010). Rodland et al (2006) suggested that these sub-daily growth patterns are controlled by internal rhythms or biological clocks, and that these mechanisms are in turn influenced by a complex interaction of physical (water temperature changes, daily light/dark cycles, tides, lunar cycle) and genetic cues (Beetjes and Williams 1985;Richardson 1988;Palmer 1995;Rodland et al 2006).…”
Section: Discussionmentioning
confidence: 99%